Effects of Climatic, Chemical, and Cultural Control Strategies on Community Composition of Auchenorrhyncha and Population Dynamics of Two Major Green Leafhopper Pests in Peach Orchards - Patrícia Monteiro Nascimento; Ana Carina Neto; Vera Guerreiro; Anabela Barateiro; Hugo Anjos; José Pereira Coutinho; Marília Antunes; Maria Teresa Rebelo (Agronomy)
A three-year study in two Mediterranean peach orchards monitored Auchenorrhyncha species, including the main vectors of plant pathogens causing significant economic losses. The research focused on the management of two polyphagous leafhoppers, Asymmetrasca decedens and Hebata (Signatasca) solani. Yellow sticky traps were used to track species dynamics and assess population trends in relation to meteorological factors such as temperature, rainfall, and humidity. Chemical treatments and early green pruning were evaluated for pest control effectiveness. Fifty-five Auchenorrhyncha species were identified, including vectors of Xylella fastidiosa. H. solani appeared from spring to early summer, and was gradually replaced by A. decedens, which peaked in late summer. Higher temperatures favoured A. decedens, while rainy days significantly reduced its presence. H. solani responded less consistently to meteorological factors, but increased with higher minimum relative humidity, and decreased with higher total humidity. These results highlight the need for targeted chemical control strategies to manage A. decedens during its peak season and the benefits of early green pruning to protect susceptible trees in spring. The results emphasise the role of climate in pest dynamics and provide important insights for IPM programmes to reduce economic losses in Mediterranean peach orchards worldwide.